Adaptasi Kurikulum Pada Mata Pelajaran IPA di Sekolah Dasar Inklusi Banda Aceh - Aishah; Sa’ud, Udin Syaefudin; Meirawan, Danny; Nurdin, Diding (Postgraduate, University of Mataram, 2024)
The inclusive education programme is a step towards implementing the mandate of the 1945 Constitution and eliminating discrimination in the education system in Indonesia. Through this programme, all children with various needs can learn together with other normal children in the same school. This study aims to identify the form of curriculum adaptation, especially in science subjects at SDN 25 Banda Aceh. This research uses a descriptive qualitative approach with a case study method. Data were collected through interviews, observations and documentation, with the interview subjects being a special mentor teacher and a class teacher at the school. Based on the results of interviews, observations and documentation, curriculum adaptation at SDN 25 Banda Aceh is reviewed from the adaptation aspect and the principle aspect. Curriculum adaptation can be seen in teaching modules or lesson plans accompanied by special notes and adjustments to learning outcomes for children with disabilities in accordance with the Merdeka curriculum. Learning adaptation can be seen in the presence of a special mentor teacher in the classroom and accompanied by the class teacher. Environmental adaptation is not optimal because the school is not optimal. In science learning, adaptations and modifications for children with disabilities are still limited.